Assesment of general toxicity and analgesic poroperty of several sea cucumber species - Rahman, Zury Azreen Azizul (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2004)
This study was conducted with the objective of establishing the presence of toxicity, mainly on the Central Nervous System (CNS) of both the sea cucumber species namely the Holothuria spp and Stichopus spp. Upon obtaining permission of the Fishery Department of Malaysia for sample harvesting of both the sea cucumber species, an expedition was arranged to the Perhentian Island. Sample were harvested at the Perhentian Island and transported while preserved in seawater prior to laboratory processing and experimentation. Subsequently both the sea cucumber species were extracted by organic and non-organic solvent using body fluids and body tissue samples. Body fluids were collected from the sea cucumber during the process of dissecting and washing. For body tissue, the sample was dried in hot air oven and ground into powdered form before extraction was performed with organic or non-organic solvents. The organic solvent used is petroleum ether while non-organic is distilled water. The sea cucumber was extracted and dried to form a powder. The technique used to do this is by water or ether based extraction followed by filtration, saturation and finally freeze-drying. From the sample powder extract obtained, calculation of dosage is done based on the amount of powder extract, volume solvent and body weight of mice. The sample solution is than test on mice. The tests include behavioral changes by observation, tail flick test and hot plate test. The study was conducted on 80 male swiss albino mice. The route of administration in this test is through the intraperitoneal method. The behavioral study was done on a 4 hours of observation period after administration of the extract. In this study, it was found that CNS disturbance occurs in mice with both thesea cucumber species. This effect includes changes in the attitude, restlessness, sedation, tremor, paralysis, pilo-erection, passitivity and jerky movements. In the entire research, the dosage of use is 1 Omg of powder extract per kg of mice body weight (mglkg). This dose is the startup point of toxic effect observed in this experiment. In the tail flick test, mice are checked for analgesic effect of the extract of sea cucumber. It is found that only water-based extract from the holothuria spp gives a positive result. In the hot plate test, mice are tested for their analgesic effect caused by the sea cucumber extract similar as the above.